Association of Perceived Health Competence With Cardiac Rehabilitation Initiation. Issue 2 (24th March 2023) - Hu, Jiun-Ruey; Huang, Shi; Bosworth, Hayden B.; Freedland, Kenneth E.; Mayberry, Lindsay S.; Kripalani, Sunil; Wallston, Kenneth A.; Roumie, Christianne L.; Bachmann, Justin M.
Abstract : Perceived health competence is a psychological construct defined as belief in one's ability to achieve health-related goals. We found that perceived health competence was associated with participation in outpatient cardiac rehabilitation programs among 1809 patients in the Vanderbilt Inpatient Cohort Study. Abstract : Purpose: Cardiac rehabilitation (CR), a program of supervised exercise and cardiovascular risk management, is widely underutilized. Psychological factors such as perceived health competence, or belief in one's ability to achieve health-related goals, may play a role in CR initiation. The aim of this study was to evaluate the association of perceived health competence with CR initiation among patients hospitalized for acute coronary syndrome (ACS) after adjusting for demographic, clinical, and psychosocial characteristics. Methods: The Vanderbilt Inpatient Cohort Study (VICS) characterized the effect of psychosocial characteristics on post-discharge outcomes in ACS inpatients hospitalized from 2011 to 2015. The primary outcome for this analysis was participation in an outpatient CR program. The primary predictor was the two-item Perceived Health Competence Scale (PHCS-2), which yields a score from 2 to 10 (higher scores indicate greater perceived health competence). Multiple logistic regression was used to evaluate the relationship between the PHCS-2 and CR initiation. Results: A total of 1809 VICS participants (median age: 61 yr, 39% female) with ACS were studied, of whom 294 (16%) initiated CR. The PHCS-2 was associated with a higher odds of CR initiation (OR = 1.15/point increase: 95% CI, 1.06-1.26, P = .001) after adjusting for covariates. Participants with comorbid heart failure had a lower odds of CR initiation (OR = 0.31: 95% CI, 0.16-0.60, P < .001) as did current smokers (OR = 0.64: 95% CI, 0.43-0.96, P = .030). Conclusion: Perceived health competence is associated with outpatient CR initiation in patients hospitalized with ACS. Interventions designed to support perceived health competence may be useful for improving CR participation.